The impact of social media on academic performance and interpersonal relations among health sciences undergraduates - P P. C. M. Chandrasena; I M. P. S. Ilankoon (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Social media has become a most inseparable part of young adults' lives with the rapid development of information and communication technology. The study aimed to assess the use of social media and its association with academic performance, well-being, and interpersonal relation of the health sciences undergraduates. MATERIALS AND METHODS: A descriptive cross-sectional study was conducted among undergraduates in Faculty of Allied Health Sciences (n = 220), University of Sri Jayewardenepura, Sri Lanka. Data were collected using a pretested, self-administered questionnaire and analyzed using descriptive and inferential statistics. RESULTS: The response rate was 79.5%. All undergraduates (n = 175) had social media accounts, and WhatsApp was the most frequently used social media site (96.0%), followed by Facebook (70.9%), mainly for communicating (85.1%), entertainment (83.4%), and online learning (65.7%). Most undergraduates (72.0%) spent 2-5 h daily on social media sites and followed social media 1-10 times per day (54.9%). The majority of them wished to use social media for academic purposes (94.9%), and the most preferred site for academic work was WhatsApp (65.1%). Most undergraduates' self-reported Grade Point Average (GPA) (46.3%) was <2.9. There was a statistically significant association between the mean GPA and frequencies of using social media (P = 0.02) (not daily [3.3 ± 0.3], 1-10 times a day [2.9 ± 0.4], and more than 10 times a day [3 ± 0.4]). Perceived social media addiction and duration of sleep (P = 0.02), activities of daily living (P = 0.004), and study time (P = 0.02) were found to be significantly associated. CONCLUSIONS: Despite the undergraduates' willingness to use social media for academic purposes, the frequency of using social media had a significant influence on their academic performance. This highlights the importance of guidance on effective use of social media and social media addiction to improve undergraduates' academic performance, well-being, and interpersonal relationships.